Change in Central Macular Thickness on OCT after Pan Retinal Photocoagulation - Muhammad Hamza Shahid, Faisal Rashid, Saba Tauqeer, Rabab Ali, Muhammad Talha Farooq, Nouman Aleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Proliferative diabetic retinopathy is the proliferation of retinal neo vessels due to uncontrolled diabetes mellitus and long duration of this disease that leads to advance diabetic eye disease . proliferative diabetic retinopathy is treated by pan retinal photocoagulation which reduces retinal oxygen demand by retinal photocoagulation. Retinal photocoagulation leads to the laser tissue interaction called thermal damage leading to coagulative necrosis of the retinal pigment epithelial cells as these cells contain melanin a dark pigment that has the ability to absorb light energy in argon laser spectrum. Objective: To determine the mean change in central macular thickness after pan retinal photocoagulation on optical coherence tomography of the macula in patients with proliferative diabetic retinopathy . Material & Methods: Our study was a Quasi experimental study conducted at Department of Ophthalmology, Services Hospital Lahore for duration of six months from April 2021 to September 2021. In this study 40 eyes from 40 patients with proliferative diabetic retinopathy were selected who underwent pan retinal photocoagulation in one sessions with 1500 burn marks. Patients in the age group of 15 to 70 years, male and female, with proliferative diabetic retinopathy in at least one eye with no history of ocular surgery or ocular trauma in last one year were included in this study . Optical coherence tomography of macula was performed before and four weeks after the session of pan retinal photocoagulation. CMT (central macular thickness) was measured for mean change in central macular thickness. Results: In this study , the mean age of patients was 48.68±1.52 years, and gender ratio of female to male patients was 1:0.77,The mean CMT before start of treatment that was considered as baseline was 230.55±5.0 and the mean CMT value after four weeks of pan retinal photocoagulation was 238.50±6.43. (p-value=0.001) Conclusion: No significant change in CMT was found from baseline CMT to four weeks after pan retinal photocoagulation.